Serum uric acid and prostate cancer: findings from the NHANES (2007–2020) - Yan, Yu; Lin, Hong; He, Zhiyao; Wang, Ling (Frontiers in Oncology, 2024)
BackgroundThe relationship between serum uric acid (SUA) levels and prostate cancer (PCa) remains controversial. This cross-sectional study investigated the association between SUA levels and PCa incidence.MethodsA total of 9,776 participants aged ≥40 from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2020 were included, 503 of whom had PCa. Weighted univariate logistic regression, multivariate logistic regression, and smooth-fitting curve analyses were used to analyze the association between SUA and PCa incidence. Concurrently, the fitted smoothing curves were used to explore the potential non-linear relationships. If non-linearity was observed, a recursive algorithm further calculated the inflection point.ResultsThree models were used to analyze the correlation between SUA levels and PCa incidence. All regression models demonstrated a negative correlation between SUA levels and PCa incidence (model 1: OR = 0.88, 95% CI=0.80–0.97; model 2: OR = 0.87, 95% CI=0.80–0.96; model 3: OR = 0.87, 95% CI=0.78–0.96). According to the trend test, with increasing SUA, the risk of PCa showed a downward trend (three models P for trend = 0.037, 0.015, 0.016). According to the subgroup analysis, a significant negative correlation between SUA and PCa was detected in individuals aged >60 years, non-Hispanic whites, those of other races, and those with hypertension. Moreover, the association between SUA and PCa followed a U-shaped curve among participants without hypertension, and the inflection point of SUA was 5.1 mg/dl.ConclusionsThis cross-sectional study revealed a negative relationship between SUA levels and the risk of PCa, particularly in specific demographic groups. These findings offer a fresh perspective on the role of SUA in PCa patients, potentially paving the way for new approaches for the prevention and treatment of PCa. However, further studies are necessary to validate these findings.